On‐Chip: Direct Microrolling Processing on a Silicon Wafer (Small 36/2017). Issue 36 (21st September 2017) - Aoki, Kanna; Ishiguro, Keita; Denokami, Masaki; Tanahashi, Yuya; Furusawa, Kentaro; Sekine, Norihiko; Adschiri, Tadafumi; Fujii, Minoru
Abstract : In article number 1701630, Kanna Aoki and co‐workers achieve patterning of porosified silicon wafer surfaces using anodic oxidation, and conventional photolithography and wet etching. Subsequent oxidation treatment facilitated self‐rolling in the porous silicon layers. Various three‐dimensional shapes such as bowls, tubes, and boxes were realized. A direct silicon‐processing technology that enables thin layers of silicon surfaces to be bent into various three‐dimensional curved structures at the micron scale is useful for expanding the capabilities and design possibilities of on‐chip Si devices.